2014
DOI: 10.1097/ccm.0b013e3182a639da
|View full text |Cite
|
Sign up to set email alerts
|

Renal Histopathology During Experimental Septic Acute Kidney Injury and Recovery*

Abstract: The lack of any tubular injury or increased apoptosis, the increased expression of all cortical nitric oxide synthase isoforms, and the link between inducible nitric oxide synthase and neuronal nitric oxide synthase with renal blood flow suggest in this experimental model that severe sepsis acute kidney injury can develop in the absence of histological or immunohistological changes and may be functional in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 26 publications
5
66
1
Order By: Relevance
“…18 Despite more patients with septic AKI required RRT when compared with non-septic AKI, they had better renal recovery. This finding is actually similar to that reported by Cruz et al and Bagshaw et al, 8,19 signifying a difference in the pathophysiology [20][21][22] between septic and non-septic AKI. Instead, Singer et al proposed the cell cycle arrest hypothesis and mentioned that multiorgan failure induced by critical illness is primary a functional, rather than structural abnormality.…”
Section: Discussionsupporting
confidence: 92%
“…18 Despite more patients with septic AKI required RRT when compared with non-septic AKI, they had better renal recovery. This finding is actually similar to that reported by Cruz et al and Bagshaw et al, 8,19 signifying a difference in the pathophysiology [20][21][22] between septic and non-septic AKI. Instead, Singer et al proposed the cell cycle arrest hypothesis and mentioned that multiorgan failure induced by critical illness is primary a functional, rather than structural abnormality.…”
Section: Discussionsupporting
confidence: 92%
“…This provides evidence that AGs might stop endothelial and cellular signals at the origin of sepsis-related AKI (35).…”
Section: Discussionmentioning
confidence: 79%
“…Recent pharmacological concepts of AGs administration, such as the once-daily dose schedule for AG administration, which result in a decrease on AG-associated AKI (9) have been respected in the present study, as shown by the use of once-daily doses of gentamicin and amikacin during a short course achieving a correct rate of target obtention (Table 3). A physiological mechanism has also been suggested by several authors (33)(34)(35). Lipcsey et al compared four groups of pigs (endotoxinemia plus tobramycin, endotoxinemia plus saline, saline plus tobramycin, and saline alone) and suggested that sepsis-induced hypoperfusion was predominant over specific AG toxicity for AKI occurrence (34).…”
Section: Discussionmentioning
confidence: 89%
“…These inflammation-derived reactions compromise the endothelial barrier function, activate coagulation system, and impair receptor-mediated vasoreactivity, which alter the intrarenal microcirculatory blood flow distribution, causing heterogeneous patchy micro-areas of ischemia, often in the absence of macrocirculation (renal blood flow) defect (reviewed in [4,5] ). Nitric oxide synthase overexpression (all isoforms) in the cortex during sepsis also contributes to the shunting of blood flow away from the medulla [6] , exacerbating ischemia. The areas of hypoxia are subject to reperfusion injury.…”
Section: Qianmentioning
confidence: 99%